PENGARUH PERSEPSI WAJIB PAJAK DAN PREFERENSI RISIKO TERHADAP KEPATUHAN WAJIB PAJAK - Wiwit Irawati; Arum Kumala Sari (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to examine the effect of Taxpayer Perception and Risk Preference on Taxpayer Compliance. Taxpayer compliance is a very important thing and is needed so that the state revenue in the tax sector is maximized. This research was conducted using convenience sampling with a sample of 100 respondents from individual taxpayers at the Jakarta KPP Kebayoran Baru Tiga. The data used are primary data through a questionnaire containing respondents' answers. The data analysis used in this study is multiple linear regression analysis, which includes the Determination Coefficient Test, T Test and F Test. Before the hypothesis test, the collected data will be through a data quality test consisting of Normality Test, Multicollinearity Test and Heteroscedasticity Test. The results of this study indicate that Taxpayer Perception has a positive and significant effect on Taxpayer Compliance. While Risk Preference does not affect Taxpayer Compliance. But simultaneously Taxpayer Perception and Risk Preference have a significant effect on Taxpayer Compliance